The The Influence of Non-Financial Rewards on Employee Motivation: A Reflective-Formative Hierarchical Component Model Approach - Mochammad Kevin Zola; Didin Hikmah Perkasa (Manunggal Halim Jaya, 2026)
This study aims to examine the influence of non-financial rewards on employee motivation using a Reflective-Formative Hierarchical Component Model (HCM) approach. Non-financial rewards have become increasingly important in modern human resource management as organizations recognize that financial compensation alone is insufficient to sustain long-term employee motivation. This research addresses a critical gap in the literature by conceptualizing non-financial rewards as a multidimensional higher-order construct comprising Recognition and Appreciation, Career Development Opportunity, Work Flexibility, and Supportive Work Environment. Data were collected from 162 active employees in Indonesia through an online self-administered questionnaire using purposive sampling. Structural Equation Modeling-Partial Least Squares (SEM-PLS) with a Two-Stage Approach was employed to analyze the data. The results indicate that Non-Financial Rewards have a positive and significant influence on Employee Motivation (β = 0.611; t = 15.070; p = 0.000), with a large effect size (f² = 0.597). Recognition and Appreciation (weight = 0.601; p = 0.000) and Supportive Work Environment (weight = 0.338; p = 0.012) significantly contribute to the formation of Non-Financial Rewards, while Career Development Opportunity does not (weight = 0.246; p = 0.097). Work Flexibility was excluded from the model due to poor internal consistency (Cronbach's Alpha = 0.189). The model explains 37.4% of the variance in employee motivation (R² = 0.374) and demonstrates predictive relevance (Q²predict = 0.141–0.246). This study contributes to the Self-Determination Theory literature by empirically demonstrating how non-financial rewards collectively fulfill the basic psychological needs of autonomy, competence, and relatedness. The findings provide practical implications for organizations in designing effective non-financial reward systems.